Do fim do trabalho ao trabalho sem fim: o trabalho e a vida dos trabalhadores digitais em Home Office - Oliveira, Daniela Ribeiro de (2017)
Digital workers are a privileged category for understanding current job settings in which different ways of organizing, managing, and performing work are set. The digital worker organizes his life around projects, with flexible times and his career path and permanence in the work depends on permanent updating. The objective of the research was to analyze the relationship between work and life of digital workers, trying to understand to what extent the work of software development, with various forms of organization and time-space management, reflects on the organization of workers' private lives and Family relationships, friendship, leisure, etc. Through the occupational trajectories we try to trace workers' perceptions about life and work when they are working partially or totally in home office. To meet the research objectives, we conducted 53 semi-structured interviews, of which only 29 interviews were selected for discussion in this thesis. The criterion for selection sought those that represented the diversity of the empirical field in terms of gender cut, work places, types of contractual ties, types of activities performed, size of company and because they represent a diverse picture of work experiences In home office. We note a diversity of home office work arrangements practiced by digital workers. Work is done more at home than in the office, since the workers take advantage of the times saved due to the absence of displacements, intervals of snacks and rest, to continue carrying out the activities. Turning off the computer does not mean disconnecting from the job. The feeling of loneliness and the fear of becoming invisible to the office staff are grounds for digital workers to refuse (if they have a choice) work in home office or wish to leave the modality; Workers with more career time tend to resist (micro resistance) the excesses of demands and to work going through all the free time. Male representations of the presence of women in the sector are surrounded by gender stereotypes. The justifications of which particular occupations are most appropriate for women because of their gender markers (detailed, attentive, etc.) are recurrent among men.